Estrategias publicitarias digitales de la marca Oway en la ciudad de Babahoyo - Peña Lamilla, Yoleyda Jamilex (2023)
The problem focuses on identifying the possible reasons behind the lack of effectiveness of digital advertising strategies. It must be determined if they have any defined market segmentation, if they know their public objective and if the digital advertising content is adapted to the characteristics and behavior of their followers. Some areas of analysis that should be considered include that they handle inadequate segmentation, it is also necessary to investigate whether it has correctly identified its target audience and whether digital advertising methods have been adequately adapted to the characteristics and behavior of the segmentation. The objective of this case study is to analyze the digital advertising strategies implemented by the Oway venture in the city of Babahoyo. Currently, the business environment has become highly competitive and dynamic, especially in the digital field. Bear in mind that advertising planning plays a crucial role in the success and growth of companies, since they allow reaching a broader audience, generating greater brand visibility and increasing sales. This case study provided valuable information for local entrepreneurs and people interested in the field of digital advertising.